ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PROVIDER INDOSAT OOREDOO (Studi Kasus Pada Pengguna Provider Indosat Ooredoo Yang Beraktifitas Di Wilayah Jakarta Pusat) - Naudia Syahirra (2022)
Indosat Ooredoo is a telecommunications network and service provider based in Indonesia. Consumers of the Indosat Ooredoo provider in the central business district of Jakarta are the subject of this investigation. This research is a quantitative research. There are 96 respondents in this survey, all of whom are Indosat Ooredoo customers in the Central Jakarta area. The non-probability sample was selected through purposive sampling. Data were collected through questionnaires, and analyzed using PLS3.0 smart software. Based on the results of the study, (1) product quality has a significant effect on purchasing decisions with a P value of 0.025, (2) brand image has an insignificant effect on purchasing decisions with a P value of 0.449, and (3) price has a significant effect on purchasing decisions with a P value is 0.001. Product quality, brand image, and price influence purchasing decisions with an R square value of 60.6%, while other factors such as quality of promotional services and perceived comfort contribute 39.4%. Keywords: Product Quality, Brand Image, Price, Purchase Decision. And Indosat Ooredoo.